2006
DOI: 10.1016/j.healthpol.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and administrative contextual determinants of lack of access to a regular doctor: A multilevel analysis in southern Sweden

Abstract: This study suggests that both administrative health care district and social capital may partly explain the individual's self reported lack of access to a regular doctor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…As a result, access to different forms of social protection is limited and benefits a smaller part of the population (Mesa-Lago, 2007; van Ginneken, 1999). In this context, social capital may be particularly relevant to enhance collective actions within communities, becoming a potential driver of health improvements (Aye et al, 2002; Lindstrom et al, 2006; Mohseni & Lindstrom, 2007). In support of this view, evidence suggests that cohesive communities may be more successful in protecting healthcare facilities from budget cuts (Sampson et al, 1997); organizing public services (Altschuler et al, 2004; Kawachi et al, 1997); reducing crime (Takagi et al, 2012); and promoting economic solidarity (Aye et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, access to different forms of social protection is limited and benefits a smaller part of the population (Mesa-Lago, 2007; van Ginneken, 1999). In this context, social capital may be particularly relevant to enhance collective actions within communities, becoming a potential driver of health improvements (Aye et al, 2002; Lindstrom et al, 2006; Mohseni & Lindstrom, 2007). In support of this view, evidence suggests that cohesive communities may be more successful in protecting healthcare facilities from budget cuts (Sampson et al, 1997); organizing public services (Altschuler et al, 2004; Kawachi et al, 1997); reducing crime (Takagi et al, 2012); and promoting economic solidarity (Aye et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…How patients relate to primary care is linked to choice of primary care provider [9–14]. Differences in individual preferences and options can be explained using trust and other constructs related to theories on social capital [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have created one or more social capital scales by aggregating and combining a range of individual measures such as perceived interpersonal trust and social control/cohesion, community and voting participation, and sense of personal safety and efficacy (Hendryx et al 2002;Greenberg and Rosenheck 2003;van der Linden et al 2003;Wan and Lin 2003;Drukker et al 2004;Lindströ m et al 2006). Conceived of this way, social capital has been associated with individuals reporting fewer access problems across MSAs in the United States (Hendryx et al 2002) and better access to a regular doctor in Scania, Sweden (Lindströ m et al 2006); however, other studies found that the social capital scale was only related to access or utilization through its relationship to other factors like health status (Wan and Lin 2003) or neighborhood poverty (van der Linden et al 2003;Drukker et al 2004). When individual indicators of social capital (as opposed to a scale) have been used to examine health care access, the findings have also been largely inconclusive (Aye, Champagne, and Contandriopoulos 2002;Prentice 2006).…”
mentioning
confidence: 99%